Investigation of pouring temperature and holding time for semisolid metal feedstock production - Nur Azhani, Abdul Razak; Asnul Hadi, Ahmad; Mohd Rashidi, Maarof (IOP Publishing Ltd, 2017)
Semisolid metal (SSM) processing, as a kind of new technology that exploits forming of alloys between solidus and liquidus temperatures, has attracted great attention from investigators for its thixotropic behaviour as well as having advantages in reducing porosity, macrosegregation, and forming forces during shaping process. Various techniques are employed to produce feedstock with fine globular microstructures, and direct thermal method is one of them. In this paper, the effect from different pouring temperatures and holding times using a direct thermal method on microstructure and hardness of aluminium alloy 6061 is presented. Molten aluminium alloy 6061 was poured into a cylindrical copper mould and cooled down to the semisolid temperature before being quenched in water at room temperature. The effect of different pouring temperatures of 660 °C, 680 °C, 700 °C, and holding time of 20 s, and 60 s on the microstructure of aluminium alloy 6061 were investigated. From the micrographs, it was found that the most globular structures were achieved at processing parameters of 660 °C pouring temperature and 60 s holding time. The highest density and hardness of the samples were found at the same processing parameters. It can be concluded that the most spheroidal microstructure, the highest density, and the hardness were recorded at lower pouring temperature and longer holding time.